Relaksasi Otot Progresif Untuk Menurunkan Tingkat Stres Pada Waria yang Terinfeksi HIV/AIDS - Retno Kasih Kusumastuti; Kamsih Astuti; Kondang Budiyani (LPPM Universitas Proklamasi 45, 2022)
Objective of this research is to understand the effectivity of the progressive muscle relaxation in order to decline the stress level among the HIV/AIDS infected ladymen. We propose the hypothesis that there will be a decline stress level among those HIV/AIDS ladymen just after they received the progressive muscle relaxation. Five ladymen participate in this research and their stress level are moderate untill high. Design of this research is the one group pretest-posttest. Instrument of data collection is the DASS 42 Stress Scalle. We ask participants to complete the scale just before and after receiving five times progressive muscle relaxation. This research reveals that there is a significant difference in stress level between before and after receiving five timer progressive muscle relaxation (Z = -2,032, p = .042 or p< .05). The mean scores for the stress level are 26.00 and 15.00 just before and after receiving the progressive muscle relaxation respectively. Based on that data, we come to conclusion that the progresssive muscle relaxation is effective in reducing stress level among the infected HIV/AIDS ladymen.